Analisis Aktivitas Fisik Ringan dan Berat Terhadap Kadar Hemoglobin - Heriyanto,; Indah Sari,; Aristoteles; Bastian (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Physical activity is all body movements caused by skeletal muscles with the need for energy expenditure. Physical activity is divided into 3 categories. Light, moderate and heavy physical activity. Heavy physical activity will increase metabolic activity, the acid produced in the form of hydrogen ions and lactic acid will increase a lot, this will cause a decrease in pH and intravascular hemolysis. The affinity between oxygen and hemoglobin will decrease when the blood pH is low. Hemoglobin is a tetrameric protein of erythrocytes that binds to non-protein molecules, namely iron porphyrin compounds called heme. This study aims to determine the effect of light and heavy physical activity on hemoglobin levels in students of the Faculty of Science and Technology IKest Muhammadiyah Palembang. This type of research is carried out in the form of experiments which are analyzed descriptively quantitatively and presented in the form of simple tables and diagrams. The sample was examined using a Hematology Analyzer with the Alfa Swelab Plus brand, the Pothomertic method. The results showed that the average hemoglobin level for light physical activity was 15.01g/dL and heavy physical activity was 15.2 g/dL with the One Way Anova test, the value = 0.689. The conclusion of the study showed that there was no effect between light and heavy physical activity on hemoglobin levels in students of the Faculty of Science and Technology IKest Muhammadiyah Palembang.